Excerpt from Dead Stars: American and Philippine Literary Perspectives on the American Colonization of the Philippines - Jennifer M. McMahon (Journal of Transnational American Studies, 2011)
Dead Stars: American and Philippine Literary Perspectives on the American Colonization of the Philippines examines the American colonization of the Philippines from three distinct but related literary perspectives. The first is the reaction of anti-imperialist American writers Mark Twain, W. E. B. Du Bois, and William James to America’s first foray into the role of colonizer and how their varied essays, letters, and speeches provide an incisive delineation of fundamental conflicts in American identity at the turn of the twentieth century. The book then analyzes how these same conflicts surface in the colonial regime’s use of American literature as a tool to inculcate American values in the colonial educational system. Finally, Dead Stars considers the way three early and important Filipino writers—Paz Marquez Benitez, Maximo Kalaw, and Juan C. Laya—interpret and represent these same tensions in their fiction.